One Health Evaluation of Antimicrobial Use and Resistance Surveillance: A Novel Tool for Evaluating Integrated, One Health Antimicrobial Resistance and Antimicrobial Use Surveillance Programs - Haworth-Brockman, Margaret; Saxinger, Lynora M.; Miazga-Rodriguez, Misha; Wierzbowski, Aleksandra; Otto, Simon J. G. (Frontiers in Public Health, 2021)
We describe the development, application and utility of our novel, One Health Evaluation of Antimicrobial Use and Resistance Surveillance (OHE-AMURS) tool that we created to evaluate progress towards integrated, One Health surveillance of antimicrobial resistance (AMR) and antimicrobial use (AMU) as a complex system in Canada. We conducted a qualitative inquiry into the current state of policy and programs for integrated AMR/AMU surveillance using explicit and tacit knowledge. To assess the “messy” state of public health surveillance program development, we synthesized recommendations from previous reports by the National Collaborating Centre for Infectious Diseases and the Canadian Council of Chief Veterinary Officers; conducted an environmental scan to find all federal, provincial and territorial AMR/AMU surveillance programs in Canada; and conducted semi-structured interviews with Canadian subject matter experts. To integrate evidence from these different sources we adapted two published tools to create a new evaluation matrix, deriving 36 components of the ideal integrated AMR/AMU surveillance system. Our two-way matrix tool allowed us to examine seven common, foundational elements of sustainable programs for each component, and assign a stage of development/sustainability ranking for each component according to the matrix definitions. Our adaptable novel tool allowed for granular and repeatable assessment of the many components of a complex surveillance system. The assessment proved robust and exacting to ensure transparency in our methods and results. The matrix allows flexible assignment of program components based on program principles, and stages can be adapted to evaluate any aspect of an AMR/AMU surveillance or other multi-faceted, multi-jurisdictional system. Future refinement should include an assessment of the scope of surveillance components.